Proposed new interior design scheme of traditional music instrument gallery for Jabatan Kebudayaan & Kesenian Negara (JKKN) at Lot 4118, 4119 Jalan Sultan Yusuff Izuddin, 32200 Lumut, Perak / Nor Azian Che Onn - Che Onn, Nor Azian (Faculty of Architecture, Planning and Surveying, 2011)
The final years students of Interior Architecture Diploma needs to complete the final project report at the same time to understand every aspect of the project starts from beginning until the end of the project final presentation.Today we find the world is becoming more modernise with new creation.Some times its influence human psychology either mentally and physically.This includes aspects of human consumption of all categories of gallery today helped a lot of everyday human life,especially in terms of which categories of economy.But how the retails especially the traditional music instrument retail provides help to people with the satisfaction maxsimum.My study is to entitled proposed new design scheme of traditional music instrument gallery for Jabatan Kebudayaan dan Kesenian Negara (JKKN) at lot 4118,4119 Jalan Sultan Izuddin yusuff,32200 Lumut.Perak.So i will review,complete and will explain all the problems as well as related to the topic.Jabatan Kebudayaan dan Kesenian Negara (JKKN) no longer have a space or gallery to display traditional musical instrument.So,Jabatan Kebudayaan dan Kesenian Negara (JKKN) has plans to open a traditional musical instrument gallery in one small area that is Lumut City.As we know.Lumut City has the potential to carry out these activities.Lumut is a tourist area either in country or abroad.So.i want to proposed,create,manage and understand succesful concept to achieve the Jabatan Kebudayaan dan Kesenian Negara (JKKN) targets and objectives.